Effects of Age, Sex, and Neuropsychological Performance on Financial Decision-Making - Shivapour, Sara K.; Nguyen, Christopher M.; Cole, Catherine A.; Denburg, Natalie L. (Frontiers in Neuroscience, 2012)
The capacity to make sound financial decisions across the lifespan is critical for interpersonal, occupational, and psychological health and success. In the present study, we examined how healthy younger and older adults make a series of increasingly complex financial decisions. One-hundred and sixteen healthy older adults, aged 56 to 90 years, and 102 college undergraduates, completed the Financial Decision Making Questionnaire, which requires selecting and justifying financial choices across four hypothetical scenarios and answering questions pertaining to financial knowledge. Results indicated that Older participants significantly outperformed Younger participants on a multiple-choice test of acquired financial knowledge. After controlling for such pre-existing knowledge, several additional age effects were observed. For example, Older participants were more likely to make immediate investment decisions, whereas Younger participants exhibited a preference for delaying decision-making pending additional information. Older participants also rated themselves as more concerned with avoiding monetary loss (i.e., a prevention orientation), whereas Younger participants reported greater interest in financial gain (i.e., a promotion orientation). In terms of sex differences, Older Males were more likely to pay credit card bills and utilize savings accounts than were Older Females. Multiple positive correlations were observed between Older participants’ financial decision-making and performance on neuropsychological measures of non-verbal intellect and executive functioning. Lastly, the ability to justify one’s financial decisions declined with age, among the Older participants. Several of the aforementioned results parallel findings from the medical decision-making literature, suggesting that older adults make decisions in a manner that conserves diminishing cognitive resources.